2007
DOI: 10.1038/sj.jcbfm.9600533
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortical Cell Loss and Prolonged Hemodynamic Depression after Traumatic Brain Injury in Mice Lacking the IP Receptor for Prostacyclin

Abstract: Prostacyclin is the major arachidonic acid metabolite of the vascular endothelium and is produced mainly via the cyclooxygenase-2 pathway. By acting on the prostacyclin (IP) receptor on platelets and vascular smooth muscle cells, prostacyclin exerts vasodilatory and antiaggregative/antiadhesive effects. Previous studies have shown that prostacyclin production increases after brain trauma, but the importance of prostacyclin for posttraumatic hemodynamic alterations and neuron survival has not been investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…6 In the cerebral circulation, elevated production of PGI 2 in response to vascular injury is designed to prevent aggregation of platelets, to preserve blood flow, and to inhibit aberrant remodeling of injured vascular wall. 3,34 However, no previous studies have addressed the role of PGI 2 in regulation of APP processing. Recognition of the ability of PGI 2 to regulate expression and non-amyloidogenic processing of APP suggests that this mechanism might be an important contributor to overall neurovascular protective functions of PGI 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…6 In the cerebral circulation, elevated production of PGI 2 in response to vascular injury is designed to prevent aggregation of platelets, to preserve blood flow, and to inhibit aberrant remodeling of injured vascular wall. 3,34 However, no previous studies have addressed the role of PGI 2 in regulation of APP processing. Recognition of the ability of PGI 2 to regulate expression and non-amyloidogenic processing of APP suggests that this mechanism might be an important contributor to overall neurovascular protective functions of PGI 2 .…”
mentioning
confidence: 99%
“…[1][2][3][4] The endothelium is a major source of PGI 2 which is generated in response to a number of different stimuli including vascular injury.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a potent vasodilator and inhibitor of leukocyte activation, platelet aggregation, and leukocyte-endothelial interactions, all of which are properties with a hypothetical impact on the development of DIND. 5 Animal studies and in vitro studies have demonstrated positive effects of prostacyclin on cerebral blood flow (CBF) and vasospasm, [6][7][8][9][10] and an imbalance in the prostacyclin-prostaglandin ratio has been proposed as a cause of vasospasm. 6,11 Although results from in vitro and animal studies are promising, few studies exist that investigate the possible effects of prostacyclin on cerebral…”
mentioning
confidence: 99%